2021
DOI: 10.3390/ijms222212240
|View full text |Cite
|
Sign up to set email alerts
|

Crabp1 Modulates HPA Axis Homeostasis and Anxiety-like Behaviors by Altering FKBP5 Expression

Abstract: Retinoic acid (RA), the principal active metabolite of vitamin A, is known to be involved in stress-related disorders. However, its mechanism of action in this regard remains unclear. This study reports that, in mice, endogenous cellular RA binding protein 1 (Crabp1) is highly expressed in the hypothalamus and pituitary glands. Crabp1 knockout (CKO) mice exhibit reduced anxiety-like behaviors accompanied by a lowered stress induced-corticosterone level. Furthermore, CRH/DEX tests show an increased sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These novel activities of atRA were collectedly referred to as “non-canonical” and were later found to be mediated by the Cellular Retinoic Acid Binding Protein 1 (CRABP1) [ 22 ]. These CRABP1-mediated non-canonical activities of atRA were ultimately validated in careful studies of Crabp1 knockout (CKO) mice and cultures, which also revealed the physiological/disease relevance of CRABP1 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introduction: Canonical and Non-canonical Activities Of All-...mentioning
confidence: 89%
See 2 more Smart Citations
“…These novel activities of atRA were collectedly referred to as “non-canonical” and were later found to be mediated by the Cellular Retinoic Acid Binding Protein 1 (CRABP1) [ 22 ]. These CRABP1-mediated non-canonical activities of atRA were ultimately validated in careful studies of Crabp1 knockout (CKO) mice and cultures, which also revealed the physiological/disease relevance of CRABP1 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introduction: Canonical and Non-canonical Activities Of All-...mentioning
confidence: 89%
“…In examining the systemic inflammatory status/potential of CKO mice, it was found that HFD-fed CKO mice all had increased systemic inflammation, indicated by invading immune cells in adipose tissue [ 28 ], increased inflammatory driver Receptor Interacting Protein 140 (RIP140) (gene name Nrip1) [ 68 ] in the blood [ 31 ], elevation in inflammatory cytokines, and significantly enhanced macrophage M1 polarization (unpublished). Previous studies also indicated that CKO mice had overall increased inflammation in the heart, indicated by increased cardiac fibrosis [ 26 ], and an altered anxiety and stress response in their HPA axis [ 32 ]. To this end, CRABP1 was found to be involved in exosome secretion from CRABP1-expressing neurons.…”
Section: Crabp1-signalsomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A compelling body of evidence implicates that the activation of the HPA axis and pulsatile release of glucocorticoids play critical roles in response to physical or psychological stressors in physiological status (6). A growing literature has implicated that the HPA axis contributes to the development of psychiatry disorders, such as depression, anxiety, and PTSD (7)(8)(9). Animal studies suggested that the HPA axis dysfunction caused by environmental components could induce autism-like behaviors, and regulation of the HPA axis could alleviate autism-like behaviors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Besides binding RA, CRABP1 is known to modulate at least two cytosolic signaling, MAPK and CaMKII, pathways in a cell context-dependent manner [ 22 ]. While its functional roles in several cell types have been uncovered recently, including neuron differentiation [ 23 ], neuronal exosome secretion [ 24 ], endocrine homeostasis [ 25 ], and cardiomyocyte function [ 26 ], how CRABP1 functions specifically in adipocytes remain elusive. Importantly, we have found that Crabp1 gene expression is tightly regulated during adipocyte differentiation, through hormonal induction followed by epigenetic silencing [ 27 ].…”
Section: Introductionmentioning
confidence: 99%